Dynamic Geometry: P95

Geometry Level 4

The diagram shows a black semicircle with radius 1 1 . The cyan and green semicircle are growing and shrinking freely on the black semicirle's diameter. The purple circle is internally tangent to the black semicircle and tangent to both green and cyan semicircle. The red and orange circles are internally tangent to the black semicircle and tangent to the purple circle and to one of the bottom semicircles. The tangency points between the orange circle, the red circles and the bottom semicircles trace a locus (blue curve). The area bounded by the blue curve and the black semicircle's diameter can be expressed as:

p q tan 1 ( m n ) n m \frac{p}{q} \cdot \tan^{-1}\left(\frac{m}{n}\right)-\frac{n}{m}

where p p , q q , m m and n n are positive integers. p p and q q are coprime so are m m and n n . Find p + q + m + n 3 \sqrt[3]{p+q+m+n} .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Mar 27, 2021

Let the center of the unit semicircle be O ( 0 , 0 ) O(0,0) , the origin of the x y xy -plane, and its diameter A B AB , the center of the purple circle be P P , P O B = θ \angle POB = \theta , and t = tan θ 2 t = \tan \frac \theta 2 . Also let an arbitrary point on the locus or the tangent point of the cyan semicircle and orange circle be T 1 ( x , y ) T_1(x,y) . From the calculations in Dynamic Geometry: P80 Series , we have:

{ x = 13 t 2 t 2 + 4 t + 13 y = 6 t t 2 + 4 t + 13 \begin{cases} x = \dfrac {13-t^2}{t^2+4t+13} \\ y = \dfrac {6t}{t^2+4t+13} \end{cases}

Then the area under the locus is given by

A = 2 0 t = 13 x d y = 2 0 t = 13 13 t 2 t 2 + 4 t + 13 d ( 6 t t 2 + 4 t + 13 ) = 2 0 13 13 t 2 t 2 + 4 t + 13 6 ( 13 t 2 ) ( t 2 + 4 t + 13 ) 2 d t = 12 0 13 ( 13 t 2 ) 2 ( t 2 + 4 t + 13 ) 3 d t = 13 9 tan 1 3 2 2 3 \begin{aligned} A & = 2 \int_0^{t=\sqrt{13}} x \ \ce dy \\ & = 2 \int_0^{t=\sqrt{13}} \frac {13-t^2}{t^2+4t+13} \ce d \left(\frac {6t}{t^2+4t+13} \right) \\ & = 2 \int_0^{\sqrt{13}} \frac {13-t^2}{t^2+4t+13} \cdot \frac {6(13-t^2)}{(t^2+4t+13)^2} \ce dt \\ & = 12 \int_0^{\sqrt{13}} \frac {(13-t^2)^2}{(t^2+4t+13)^3} \ce dt \\ & = \frac {13}9 \tan^{-1} \frac 32 - \frac 23 \end{aligned}

Therefore p + q + m + n 3 = 13 + 9 + 3 + 2 3 = 3 \sqrt[3]{p+q+m+n} = \sqrt[3]{13+9+3+2} = \boxed 3 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...